LAND COVER – RELIEF RELATIONSHIPS AND ENVIRONMENTAL RISK EVALUATION IN SOROCABA – SP - Silva, Alexandre Marco da; Paula, Fabíolla Pereira de; Ikematsu, Priscila; Silveira, Felipe Muniz; Nogueira, Davi Pajaro; Bomback, Michele; Alves, Sérgio Henrique; Haddad, Marcello (Caminhos de Geografia, 2007)
Considering the crucial role that the relief plays in the landscape dynamics and also considering that the land use / land cover patterns might be a driving force in starting some kinds of environmental impacts, this paper examines the occurrence of the land cover classes in relation the slope categories along the Sorocaba city (SP), and analyses the adequacy of such distribution. This study was carried out through GIS technology and using two main databases: the first one was the digital land cover map for 2003 and the second one was the Digital Elevation Model of the study area (converted into slope map). These two maps were crossed and the resulting map shows that the city presents a predominance of adequate land cover (78.9%). However, approximately 11% of the study area indicates having some type of risk due to incompatibility of the land cover and relief, showing that the land use should be reorganized in these risky areas. The use of soil conservation practices along the agricultural areas and terracing in urban settlements are initiative that should be implemented in order to mitigate or, preferably, eliminate the impacts.